2017
DOI: 10.1159/000454805
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Metabolic Responses to a Single Bout of Resistance Exercise in Prader-Willi Syndrome

Abstract: Background: Prader-Willi syndrome (PWS) is characterized by excessive adiposity. Excess adiposity negatively affects hormonal and metabolic responses to aerobic exercise. This study determined whether PWS and/or adiposity affected hormonal and metabolic responses to resistance exercise. Methods: Eleven children with PWS (11.4 ± 3.1 years, 43.9 ± 7.5% body fat), 12 lean children (9.3 ± 1.4 years, 18.3 ± 4.9% body fat), and 13 obese children (9.6 ± 1.3 years, 40.3 ± 5.2% body fat) participated. The children step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The findings on hormonal responses to exercise are inconsistent across studies; however, differences between study protocols performed and the limited sample sizes could have contributed to these discrepancies . The two studies that analysed the hormonal response to exercise were conducted in children and adolescents .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings on hormonal responses to exercise are inconsistent across studies; however, differences between study protocols performed and the limited sample sizes could have contributed to these discrepancies . The two studies that analysed the hormonal response to exercise were conducted in children and adolescents .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 483 studies were identified, of which 447 did not meet the inclusion criteria. Twenty-two studies, 10,15,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] whose details are summarized in Tables 2 and 3 Mullins (1987)…”
Section: Participants' Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations